2016
DOI: 10.1590/0034-737x201663060011
|View full text |Cite
|
Sign up to set email alerts
|

Drying time and post-harvest quality of onion bulbs submitted to artificial curing

Abstract: RESUMO Drying time and post-harvest quality of onion bulbs submitted to artificial curingAfter harvest, onion bulbs are submitted to curing, whose objective is to provide loss of moisture in leaves and drying of outer layers (peel) of bulbs, reaching attractive external coloration and reduction in the intensity of rottenness. The objective of this study was to use an air treatment unit (ATU) -known as heat pump -as an alternative drying method, and to evaluate drying time and preservation of the chemical and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
1
7
1
Order By: Relevance
“…The control onions had a greener color than those treated in a CA. Similar results were obtained by Cardoso et al (2016) in ''Bola Precoce'' onions, who reported that this parameter is affected by curing, obtaining a higher value (a* = -2.32) for onions that were cured in the field than for those that were cured with artificial hot air (a* = -2.05) and with artificially heated and dried air (a* = -1.76). In another study, Trujillo et al (2016) reported higher values than those obtained in the present work in ''Roja Ocañera'' (a* = 20.24), ''Peruana Inca Alto del Pozo'' (a* = 21.85), ''Peruana Inca Abrego'' (a* = 22.50) and ''Peruana Inca La Playa'' (a* = 21.75) onions.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The control onions had a greener color than those treated in a CA. Similar results were obtained by Cardoso et al (2016) in ''Bola Precoce'' onions, who reported that this parameter is affected by curing, obtaining a higher value (a* = -2.32) for onions that were cured in the field than for those that were cured with artificial hot air (a* = -2.05) and with artificially heated and dried air (a* = -1.76). In another study, Trujillo et al (2016) reported higher values than those obtained in the present work in ''Roja Ocañera'' (a* = 20.24), ''Peruana Inca Alto del Pozo'' (a* = 21.85), ''Peruana Inca Abrego'' (a* = 22.50) and ''Peruana Inca La Playa'' (a* = 21.75) onions.…”
Section: Resultssupporting
confidence: 84%
“…Other authors have reported lower results in ''Crioula Roxa'' purple onions (Berno et al 2014) and in ''Roja Ocañera'', ''Peruana Inca Alto del Pozo'', ''Peruana Inca Abrego'' and ''Peruana Inca La Playa'' red onions (Trujillo et al 2016). Cardoso et al (2016) also reported lower values of superficial L* in ''Bola Precoce'' onions (L* = 67.96 on average) to those obtained in the present work, reporting that curing had no effect on this parameter. The onions stored in CA kept their luminosity practically constant throughout the conservation time.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Significant difference between T1 (103.04%) and T2 (19.89%) on day zero was verified, and after 14 days of storage, the values of 55.95% and 11.10% for T1 and T2, respectively, were obtained (Table 2); this occurred due to the passage of cooled air under the onion bulbs, removing moisture from the external leaves, resulting in drying these layers. According to Cardoso et al (2016), ventilation and heat allow the external leaves of the bulbs to be dried offering more effective protection against water loss in inner layers. Treatments T1 and T2 showed significant fresh weight loss over 14 days of storage (0.14 and 1.06%), as observed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…After natural cure in a shed (Cardoso et al, 2016), bulbs were selected, defective and rotten bulbs were removed.…”
Section: Methodsmentioning
confidence: 99%